PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK DAN PENGAWASAN KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA PEMERINTAH DAERAH (Studi Kasus Pada Inspektorat Provinsi Maluku Dan Kota Ambon) - Mahendra Rupilu; Linda Grace Loupatty, Yuyun yuniarti Layn (CV. Adiba Aisha Amira, 2024)
This research aims to test and analyze whether the implementation of public sector accounting and monitoring the quality of financial reports has an effect on the accountability of the financial performance of the Maluku Province regional government. This research was conducted at the Maluku Provincial Inspectorate Office and the Ambon City Inspectorate Office. This type of research is quantitative research using primary data, where data is obtained using survey data collection techniques using questionnaires. And given to 37 auditors at the Maluku Provincial Inspectorate Office and the Ambon City Inspectorate Office. Data analysis uses multiple linear regression statistical analysis (multiple regression analysis). The results of the study show that the implementation of public sector accounting has a positive and significant influence on the accountability of local government performance and supervision of the quality of financial reports has a negative and insignificant influence on the accountability of local government performance.